PERENCANAAN LAYANAN BIMBINGAN KELOMPOK DENGAN MENGGUNAKAN METODE PROBLEM SOLVING DALAM MENINGKATKAN KETERCAPAIAN TUGAS PERKEMBANGAN (STUDI ANALISIS DESKRIPTIF DI KELAS XII MIPA 3 SMAN 5 PARIAMAN) - Husni, Asy Syifa; Putra, Fuaddillah; Chandra, Yasrial (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
This research is motivated by the existence of students who have not yet achieved their developmental tasks well. The aim of this research is to find out: 1) An overview of the achievement of students' developmental tasks in class XII MIPA 3, 2) Planning for group guidance services using problem solving methods to increase the achievement of developmental tasks. This research was conducted using descriptive analysis methods. The population in this study was 24 students and the sample in this study was 24 samples. Sampling in this study used a total sampling technique. The instrument used in this research is the developmental task inventory (ITP). The analysis in this research uses a computer processing system that has been programmed in the developmental task inventory (ITP) application.The results of the research show that: 1) The description of the achievement of developmental tasks for class group guidance using problem solving methods. Based on this research, it is recommended that adolescents be able to complete their developmental tasks well in order to achieve their developmental tasks to enter the developmental stage in adulthood.